PERANCANGAN BUKU PEMANFAATAN LAHAN PEKARANGAN SEMPIT DI PERKOTAAN - FARHAN OMARA, Hendra Ariwan, S.Sn., M.Sn Drs. Yusron Wikarya, M.Pd. (DEKAVE : Jurnal Desain Komunikasi Visual, 2019)
The design aims to design a book with the theme the use of limited yard in urban areas according to the module of BPTP, West Sumatera.The method that used in designing of this book is through the Glass Box approach, with the analysis used is 5W + 1H (what, who, where, when, why and how) to find a solution to the problem.This design produced a book on the Utilization of limited Yard in Urban Areas entitled Narrow Yard Planting Models, and other supporting media, that are: posters, x-banners, aprons, t-shirts, stickers and feeds on social media (Instagram), as media support and campaign.Keyword: Book, Utilization, Narrow Yard